2002
DOI: 10.1002/bem.10063
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin‐dependent cyclic nucleotide phosphodiesterase activity is altered by 20 μT magnetostatic fields

Abstract: Absorbance measurements at 660 nm of calmodulin (CaM) dependent cyclic nucleotide phosphodiesterase activity under cell free conditions indicate that 30-min exposures to weak magnetostatic field intensities alters this activity, compared to zero magnetic field exposures. This effect depends nonlinearly on the concentration of free calcium, with maximum magnetic interaction apparently occurring at an optimal Ca(2+) concentration corresponding to 50% activation (EC(50)). If one regards Ca(2+)/CaM activation as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 12 publications
5
39
0
Order By: Relevance
“…Results obtained in the present investigation supports the earlier observations, which had reported the occurrence of oxidative/nitrosative stress in response to the MF exposure (Li and Chow 2000;Noda et al 2000;Kabuto et al 2001;Lee et al 2004), including effects on cell signaling processes (Liboff et al 2003;Zhang et al 2010) and carcinogenic effects (Bayazit et al 2010). Previous studies suggest that static and time-varying electric and MFs exposure caused oxidative DNA damage (Ivancsits et al 2003;Yokus et al 2005), increased plasma, liver, lung and kidney TBARS and SOD levels (Harakawa et al 2005;Guler (Jelenkovic et al 2005;Di Loreto et al 2009) altered cell proliferation , cortical serotonergic neurotransmission (Janac et al 2009) and memory impair (Jadidi et al 2007) in various biological organisms.…”
Section: Discussionsupporting
confidence: 92%
“…Results obtained in the present investigation supports the earlier observations, which had reported the occurrence of oxidative/nitrosative stress in response to the MF exposure (Li and Chow 2000;Noda et al 2000;Kabuto et al 2001;Lee et al 2004), including effects on cell signaling processes (Liboff et al 2003;Zhang et al 2010) and carcinogenic effects (Bayazit et al 2010). Previous studies suggest that static and time-varying electric and MFs exposure caused oxidative DNA damage (Ivancsits et al 2003;Yokus et al 2005), increased plasma, liver, lung and kidney TBARS and SOD levels (Harakawa et al 2005;Guler (Jelenkovic et al 2005;Di Loreto et al 2009) altered cell proliferation , cortical serotonergic neurotransmission (Janac et al 2009) and memory impair (Jadidi et al 2007) in various biological organisms.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, numerous studies have explored the interaction of man-made static and alternating magnetic fields with biological systems. Previous research showed that these magnetic fields can induce changes in behavior (Rudolph et al, 1985;Prato et al, 1996;Janac et al, 2005), enzyme activity (Nossol et al, 1993;Blank and Soo, 1996;Liboff et al, 2003;Chen et al, 2009), the synthesis and release of neurohormons (Peric-Mataruga et al, 2008), biophysical properties of neurons (McLean et al, 1995;Calvo and Azanza, 1999;Ye et al, 2004;Todorovic et al, 2007), synaptic transmission (Rosen, 1992) and ion channel currents (Shen et al, 2007). Furthermore, magnetic field influence on nucleic acids and protein synthesis has been found (Cridland et al, 1999;Ciombor et al, 2002;Hirai et al, 2002;Schmitz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In most cellular models the ELF-EMF-induced effects are found in the intracellular calcium variations [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%